Current concepts of anti-EGFR targeting in metastatic colorectal cancer - Doleschal, Bernhard; Petzer, Andreas; Rumpold, Holger (Frontiers in Oncology, 2022)
Anti- EGFR targeting is one of the key strategies in the treatment of metastatic colorectal cancer (mCRC). For almost two decades oncologists have struggled to implement EGFR- antibodies in the continuum of care of mCRC. Both sidedness and RAS mutational status rank high among the predictive factors for the clinical efficacy of EGFR inhibitors. A prospective phase III trial has recently confirmed that anti-EGFR targeting confers an overall survival benefit only in left sided RAS-wildtype tumors when given in first line. It is a matter of discussion if more clinical benefit can be reached by considering putative primary resistance mechanisms (e.g., HER2, BRAF, PIK3CA, etc.) at this early stage of treatment. Although, the value of this procedure in daily routine clinical utility has not yet been clearly delineated. Re-exposure to EGFR antibodies becomes increasingly crucial in the disease journey of mCRC. The value of re- induction or re- challenge strategies were erratic before, relying on mathematical models that describe the timely decay of EGFR antibody resistant clones. The advent of liquid biopsy and the implementation of more accurate next-generation sequencing (NGS) based high throughput methods allows for tracing of EGFR resistant clones in real time- displaying the spatiotemporal heterogeneity of metastatic disease- compared to the former standard (radiographic assessment and re-biopsy). These techniques may move EGFR inhibition in mCRC into the area of precision medicine in order to apply EGFR antibodies with the increase or decrease of EGFR resistant clones. This review critically discusses established concepts of tackling the EGFR pathway in mCRC and provides insight into the growing field of liquid biopsy guided personalized approaches of EGFR inhibition in mCRC.